Balancing irreversible capacity in germanium nanoparticle: HE5050 lithium ion batteries for improved energy densities exceeding 250 Wh/kg. (1st February 2020) - Staub, Jason W.; Dzara, Michael J.; Crompton, Kyle R.; Ganter, Matthew J.; Landi, Brian J.
Abstract: Matching the irreversible capacity loss of high capacity anodes and cathodes is demonstrated as a viable strategy for achieving enhanced gravimetric energy density lithium ion batteries. Germanium nanoparticle anodes enabled by single walled carbon nanotube additives (Ge-NP-SWCNT), were paired with 0.49Li2 MnO3 ·0.51LiNi0.37 Co0.24 Mn0.39 O2 – (HE5050-SWCNT) cathodes such that the irreversible charge loss of the Ge-NP-SWCNT anode has been improved (∼18%) to now closely match that of the capacity charge loss of the HE5050-SWCNT cathode (∼20%). The HE5050 and Ge-NP composites using SWCNTs retained a near identical percentage of capacity at effective C/10, C/5, C/2, 1C and 2C rates in half cells vs lithium. Calculations based on half-cell measurements predicted a full cell first cycle coulombic efficiency of ∼70% (subsequent cycling capacity retention of 100%), these predictions were confirmed with full cell testing. When paired together, the HE5050:Ge-NP full cells achieved similar capacity retention at each rate, to include ∼50% of C/10 capacity at 2C. Finally, a 4.4 mAh/cm 2 coin cell has achieved over 600 cycles at 20% depth of discharge (DOD) under low earth orbit (LEO) cycling conditions. Simple matching of high capacity Ge-NP anodes with the lithium rich HE5050 cathodes results in a charge balance without the need to pre-lithiate or use excess active material, and demonstrates a pathway to an increased energy density of 250 Wh/kg and beyond.